If your question means:
cos ( 3 π / 2 + x ) = sin x
then
cos ( 3 π / 2 + x ) = cos ( 2 π / 2 + π / 2 + x ) =
cos [ π + ( π / 2 + x ) ]
Use identity:
cos ( π + θ ) = - cos θ
In this case:
cos [ π + ( π / 2 + x ) ] = - cos ( π / 2 + x )
Now
cos [ π + ( π / 2 + x ) ]
becomes
- cos ( π / 2 + x )
Now use identity:
cos ( π / 2 + θ ) = - sin θ
In this case:
cos ( π / 2 + x ) = - sin x
That's why:
- cos ( π / 2 + x ) = - ( - sin x ) = sin x
Prove this identity.
cos(3π/s +x) = sin x
2 answers
or
using cos(A+B) = cosAcosB - sinAsinB
cos(3π/2 + x) = cos 3π/2 cosx - sin 3π/2 sinx
= 0 cosx - (-1)sinx
= sinx
using cos(A+B) = cosAcosB - sinAsinB
cos(3π/2 + x) = cos 3π/2 cosx - sin 3π/2 sinx
= 0 cosx - (-1)sinx
= sinx